Proximal-type epithelioid sarcoma—unusual presentation: unilateral vulvar mass. (9th April 2015) - Rodrigues, Ana Isabel; Lopes, Helena Isabel; Lima, Olinda; Marta, Susana
Abstract : Epithelioid sarcoma of the vulva is a very rare malignant soft tissue tumour, usually initially asymptomatic, which simulates a variety of benign lesions, leading to diagnosis only at later stages. Prognosis is generally poor. We report a case of a 55-year-old postmenopausal woman, who presented with rapid growth of an asymptomatic mass located in the left labia majora. Biopsy of the lesion revealed features characteristic of proximal-type epithelioid sarcoma. Ganglionar, adrenal, pulmonary and hepatic metastases were found at thoracoabdominopelvic CT scan. During hospitalisation, the patient's clinical condition suffered rapid deterioration and she died on the 16th day of admission.